Analisis Tindak Tutur Perlokusi Antartokoh pada Novel "Gadis Kretek" Karya Ratih Kumala - Dasilva, Antonius; Djuli, Labu; Malay, Narantoputrayadi Makan (Jurnal Lazuardi, 2025)
This research focuses on the form, function, and meaning of perlocution speech between characters in the novel "Kretek Girl" by Ratih Kumala. The purpose of this study is to describe the perlocution speech that occurs in the novel, including the stages of exploration, peak, and dissolution. The data analyzed was in the form of dialogue quotes containing perlocution speech in the novel "Kretek Girl". The method used is qualitative descriptive, with data analysis presented descriptively. This study refers to John L. Austin's theory of perlocutive speech as the basis for the analysis. The results of the study showed that there were 16 forms of perlocutive speech, such as telling, calming, asking, convincing, anxiety, promise, suggestion, confirming, affirming, offering, prohibition, invitation, praise, small talk, worry or feeling afraid, and threats. The effects caused by this act of speech are varied, including not carrying out orders, refusing, carrying out orders, accepting invitations, receiving suggestions, and not taking action.